Fintech : Financial Inclusion or Exclusion? - Tok, Yoke Wang.; Heng, Dyna. (Washington, D.C. : International Monetary Fund, 2022)
This paper examines the role of Fintech in financial inclusion. Using Global Findex data and emerging fintech indicators, we find that Fintech has a higher positive correlation with digital financial inclusion than traditional measures of financial inclusion. In the second stage of our empirical investigation, we examine the key factors that are correlated with the Fletcher School's three digital divide - gender divide, class (rich-poor) divide and rural divide. The results indicate that greater use of fintech is significantly associated with a narrowing of the class divide and rural divide but there was no impact on the gender divide. These findings imply that Fintech alone may not be sufficient to close the gender gap in access to financial services. Fintech development may need to be complemented with targeted policy initiatives aimed at addressing the gender gap directly, and at changing attitudes and social norms across demographics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Development; Financial Inclusion; Fintech; Inequality